OPTIMASI DAN KARAKTERISASI a-AMILASE DARI ISOLAT AKTINOMISETES YANG BERASAL DARI KALIMANTAN TIMUR - Soeka, Yati Sudaryati (Research Center for Biology-Indonesian Institute of Sciences, 2010)
Forty-one actinomycetes isolates from East Kalimantan held in Microbiology Division Collection-UPI, and their ability to produce a-amylase has been assessed. Those 41 number of actinomycetes isolates performed amylolytic activity as shown by clear zone areal after being poured with iodium solution. The bacteria produced high a-amylase when was grown in media containing starch soluble 2% the a-amylase activity in media containing 8.24 U/ml. The isolate (number 7) was the most active compared to another (number 100) and it was identified as Nocardia; the activity of this enzyme obtained was 12.93 U/ml (one unit activity is defined as mol of glucose produced per ml per minute). The maximum temperature for enzyme reaction was 40Â°C, optimum pH was pH 7.5 the a-amylase activity were 15.76 U/ml and 31.11 U/ml, respectively. From kinetic characterization study, it was found that enzyme showed Km and Vmax value of 7.62 % (b/v) and 71.10- umol/ml/minute respectively at condition of temperature 40Â°C, pH 7.5 and incubation time 10 minute.